Shear Bond Strength of Indirect Composites Luted with Three New Self-Adhesive Resin Cements to Dentin - TÜRKMEN, CAFER (TAYLOR & FRANCIS LTD, 2009)
The aim of this study was to evaluate the shear bond strengths of indirect composites (those cured outside the mouth) luted by three different, recently developed, self-adhesive resin cements to dentin. Seventy caries-free mandibular third molar teeth embedded in acrylic resin and with exposed dentin surfaces were used. Teeth were randomly divided into seven groups. The following application protocols were carried out: a) Group 1 (control group)direct composite resin restoration (Alert) with total-etch adhesive system (Bond 1 primer/adhesive); b) Group 2indirect composite restoration (Estenia) luted by a resin cement (Cement-It) combined with the same total-etch adhesive; c) Group 3direct composite resin restoration with self-etch adhesive system (Nano-Bond); d) Group 4indirect composite restoration luted by the resin cement combined with the same self-etch adhesive; e) Groups 5-7indirect composite restoration luted with self-adhesive resin cements (RelyX Unicem (R), Maxcem (R), and Embrace WetBond (R), respectively) onto untreated dentin surfaces. Shear bond strengths of the groups were performed with a universal testing device. Results were statistically analysed by student-t and one way ANOVA tests. The fractured surfaces were also examined by SEM. The indirect composite restorations luted with the self-adhesive resin cements (Groups 5-7) showed successful results compared with the other groups (p0.05). Group 4 showed the weakest bond strength (p0.05). Open dentin tubules were observed on the total-etch adhesive applied surfaces whereas a smear rich layer was found by SEM on the self-etch adhesive applied surfaces. The new universal self-adhesive resins may be considered an alternative for luting the indirect composite restorations onto the untreated dentin surfaces.
Keywords: Bond strength; Dentin; Indirect composite; Resin cement; Self-adhesive resin; IN-VITRO; LUTING AGENTS; ENAMEL; MICROLEAKAGE; RESTORATIONS; DEGRADATION; SYSTEMS